RETORIKA VISUAL IKLAN SOSIAL MEDIA KOLABORASI VINDES DAN RANS ENTERTAINMENT DALAM ACARA TIBA-TIBA TENIS - Widyanira, Shelyn; Zpalanzani Mansoor, Alvanov; Satria, Firmanda (Kartala, 2023)
Marketing strategy is a fundamental element for companies and media to introduce events to their target consumers. Collaboration is a widely used marketing strategy in the entertainment industry, where parties come together to generate integrated creativity and synergy. The advertisements in the Tiba-Tiba Tenis campaign, created by VINDES in partnership with RANS Entertainment on social media, exemplify collaboration in advertising and marketing. Tiba-Tiba Tenis, organized by VINDES in 2022 as part of the VINDES Sport segment, represents the implementation of Visual Communication Design, specifically in conveying persuasive messages through visual media to stakeholders. Through content analysis and the visual rhetoric theories of Sonja K Foss, Hesford, and Brueggemann, this research examines the photography and videography of the campaign using observation techniques and literature review. The findings demonstrate that the presented content not only promotes the event but also serves as educational media about tennis for VINDES and RANS Entertainment fans. The content showcases visual rhetoric that extends beyond design elements or images, incorporating cultural elements and the meanings conveyed by the visual artwork.